ANALISIS SEMIOTIKA ESTETIKA VISUAL DAN RUANG SIMBOLIK DALAM MV "GOD’S MENU" STRAY KIDS: A SEMIOTIC ANALYSIS OF VISUAL AESTHETICS AND SYMBOLIC SPACE IN STRAY KIDS’ "GOD’S MENU" MV - Shannon Devona Arihanto; Shienny Megawati Sutanto (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2025)
A Semiotic Analysis of Visual Aesthetics and Symbolic Space in Stray Kids’ "God’s Menu" MV. The phenomenon of K-pop has evolved not only as a global entertainment form but also as a complex practice of visual culture. Music videos serve as strategic media for constructing group identity through the combination of visual, spatial, and symbolic elements. This study aims to explore how spatial construction and visual elements in Stray Kids’ God’s Menu function as a system of signs forming a visual narrative that represents the group’s identity as a self-producing artist. Employing a descriptive qualitative approach and Roland Barthes’ semiotic theory, the analysis focuses on three layers of meaning: denotation, connotation, and myth. Data were collected through in-depth visual observation of the official music video and relevant documentation analysis. The findings reveal that visual elements: color, costume, setting, composition, and symbols interconnect to form a unified meaning system that emphasizes Stray Kids’ work ethic, independence, and creative identity. The dominant palette of red, black, and white conveys intensity and competitiveness, spatial settings illustrate structured production dynamics, and kitchen-related symbols function as metaphors of creativity and collaboration. Altogether, these signs construct an ideology of autonomy and professionalism within the entertainment industry. This study highlights the crucial role of visual communication design in shaping meaning and ideology within popular culture through an integrated and symbolic visual language.